Prescription Appropriateness of Drugs for Peptic Ulcer and Gastro-Esophageal Reflux Disease: Baseline Assessment in the LAPTOP-PPI Cluster Randomized Trial - Ardoino, Ilaria; Casula, Manuela; Molari, Giulia; Mucherino, Sara; Orlando, Valentina; Menditto, Enrica; Franchi, Carlotta (Frontiers in Pharmacology, 2022)
Background: Drugs for peptic ulcer and gastro-esophageal reflux disease (GERD) are among the most widely prescribed, frequently without appropriate indications. This represents an important issue, as it leads to unnecessary costs and risk of adverse events. Aim: To assess the prescription appropriateness of drugs for GERD, in the frame of the “Evaluation of the effectiveness of a Low-cost informative intervention to improve the Appropriate PrescripTiOn of Proton PumP Inhibitors in older people in primary care: a cluster-randomized controlled study” (LAPTOP-PPI) (Clinicaltrial.gov: NCT04637750) Methods: The appropriateness of drug prescription was assessed on data collected in administrative databases, by integrating information on concomitant medications, outpatient medical and laboratory procedures and hospital discharge diagnoses, according to the reimbursement criteria provided by the Italian Medicine Agency. We analyzed data of community-dwelling people aged 65 years and over, living in the areas of Bergamo (Northern Italy) and Caserta (Southern Italy), from July 1 to December 31, 2019. Results: Among 380,218 patients, 175,342 (46.1%) received at least one prescription of drugs for GERD. All in all, we found that only 41.2% of patients received appropriate prescriptions. Conclusion: Given the potential risk of adverse drug reactions, especially in older people, more educational interventions should be prompted for physicians, in order to improve the quality of prescription of drugs for GERD and, in turn, avoid unfavorable health outcomes and unnecessary costs.